Isotopic composition of Mg and Fe in garnet peridotites from the Kaapvaal and Siberian cratons. (1st March 2017) - An, Yajun; Huang, Jin-Xiang; Griffin, W.L.; Liu, Chuanzhou; Huang, Fang
Abstract: We present Mg and Fe isotopic data for whole rocks and separated minerals (olivine, clinopyroxene, orthopyroxene, garnet, and phlogopite) of garnet peridotites that equilibrated at depths of 134–186 km beneath the Kaapvaal and Siberian cratons. There is no clear difference in δ 26 Mg and δ 56 Fe of garnet peridotites from these two cratons. δ 26 Mg of whole rocks varies from −0.243‰ to −0.204‰ with an average of −0.225 ± 0.037‰ (2σ, n  = 19), and δ 56 Fe from −0.038‰ to 0.060‰ with an average of −0.003 ± 0.068‰ (2σ, n  = 19). Both values are indistinguishable from the fertile upper mantle, indicating that there is no significant Mg-Fe isotopic difference between the shallow and deep upper mantle. The garnet peridotites from ancient cratons show δ 26 Mg similar to komatiites and basalts, further suggesting that there is no obvious Mg isotopic fractionation during different degrees of partial melting of deep mantle peridotites and komatiite formation. The precision of the Mg and Fe isotope data (⩽±0.05‰ for δ 26 Mg and δ 56 Fe, 2σ) allows us to distinguish inter-mineral isotopic fractionations. Olivines are in equilibrium with opx in terms of Mg and Fe isotopes. Garnets have the lowest δ 26 Mg and δ 56 Fe among the coexisting mantle minerals, suggesting the dominant control of crystal structure on the Mg-Fe isotopic compositions of garnets. Elemental compositions and mineralogy suggest that clinopyroxene and garnet were produced by later metasomatic processes as they are not in chemical equilibrium with olivine or orthopyroxene. This is consistent with the isotopic disequilibrium of Mg and Fe isotopes between orthopyroxene/olivine and garnet/clinopyroxene. Combined with one sample showing slightly heavy δ 26 Mg and much lighter δ 56 Fe, these disequilibrium features in the garnet peridotites reveal kinetic isotopic fractionation due to Fe-Mg inter-diffusion during reaction between peridotites and percolating melts in the Kaapvaal craton.